Interdisciplinary insights on the future of food systems research: perspectives from the next generation of research leaders. Issue 11 (9th November 2022) - Russell, Cherie; Schram, Ashley; Salmon, Libby; Carrad, Amy; Barbour, Liza; Lacy-Nichols, Jennifer; Huse, Oliver; Machado, Priscila; Gilbert, Joshua; Zorbas, Christina; Thompson, Courtney
Abstract: Our dominant food system is a primary driver of worsening human and planetary health. Held in March 2022, the Public Health Association of Australia's Food Futures Conference was an opportunity for people working across the food system to connect and advocate for a comprehensive, intersectoral, whole-of-society food and nutrition policy in Australia to attenuate these issues. Conference themes included food systems for local and global good; ecological nutrition; social mobilisation for planetary and public good; food sovereignty and food equity. Students and young professionals are integral in transforming food systems, yet they are under-represented in the academic workforce, across publishing, scientific societies and conference plenaries. A satellite event was held to platform initiatives from early career researchers (ECR) in areas integral for improving planetary and public good. The research topics discussed in this commentary reflect sub-themes of the conference under investigation by ECR: food systems governance and regulation; local food policies; commercial determinants of health; sustainable healthy diets; and food equity and sovereignty.